"God … has sent me to Germany": Salomon Maimon, Friedrich Jacobi, and the Spinoza Quarrel. Issue 3 (September 2014) - Rosenstock, Bruce
Abstract Salomon Maimon's Versuch über die Transzendentalphilosophie [Essay in Transcendental Philosophy] (1790) challenges and reworks Kant's arguments in the Kritik der reinen Vernunft [Critique of Pure Reason] (1785, 2nd ed. 1787) about the foundations of natural science and of Newtonian physics in particular. Kant himself was impressed both with Maimon's grasp of his critical project and also with the force of his challenge to it. While Maimon's significance on the later development of German Idealism is now widely acknowledged, another aspect of Maimon's Versuch has not been fully appreciated, namely, its engagement with the central questions of the Spinozastreit [Spinoza Quarrel] that erupted in 1785 with the publication of Friedrich Heinrich Jacobi's Über die Lehre des Spinoza in Briefen an den Herrn Moses Mendelssohn [Concerning the Doctrine of Spinoza in Letters to Moses Mendelssohn]. The Spinoza Quarrel centered on whether and to what extent philosophy's rational understanding of God needs to be grounded in an unmediated and suprarational revelatory experience. This paper is the first extended effort at placing Maimon's Versuch into the context of the Spinoza Quarrel. I argue that the Spinoza Quarrel and Maimon's self‐proclaimed philosophical mission in response to it—the replacement of revealed faith by reason—deeply inform the goals he pursues in his Versuch. I show how Maimon's Versuch can be read as not only a response to Kant, but also to Jacobi's defense of the revelatory nature of sense experience in David Hume über den Glauben (1787), the book in which Jacobi offers his own skeptical challenge to Kant's Kritik. Situating Maimon's Versuch as a response to Friedrich Jacobi's David Hume allows us to understand how one of Maimon's objectives in his Versuch is to keep Jacobian Glaube [faith] at bay by demonstrating, using a revised Kantian framework, the conditions of the impossibility of experiencing miracles.